Analysis of the village financial system (SISKEUDES) in accountability of village funds and government performance in Singopadu Village - Hera Lindia DivaYani; Dian Fahriani (Institute of Computer Science (IOCS), 2023)
This village financial system (Siskeudes) was created by the Financial and Development Supervisory Agency (BPKP) in June 2015 in West Sulawesi. The Village Financial System (Siskeudes) has a crucial role in increasing the accountability of village funds and the performance of village governments. This research is a qualitative research which was carried out by means of independent interviews with the parties concerned regarding written information which discussed